Muslim Ummah: glorious past and today's reality - Abdul Razak, Mohd Abbas (2015)
During the Golden Age of Islam (750-1258), Muslims were in the forefront in conquering knowledge through scientific research, exploration and expeditions. In their pursuit of mastering new knowledge and technology, Muslims were prepared and opened to the idea of learning all that is positive from the earlier civilizations. As such, they borrowed ideas from the Indians, Persians and Greeks as a way of enriching their own civilization. Adopt, adapt and assimilate or integrate was the approach used by early Muslim scholars in taking knowledge from those outside the Islamic faith. This meticulous and selective approach in taking ideas from others and adapting those ideas without contradicting the Islamic metaphysical framework (aqa’id) in a way enriched the Islamic civilization.